Russian literary and philological journals: History and the present - N. N. Misjurov; E. V. Teslja (Библиосфера, 2013)
The article reveals the history and current status of national magazines in Russia on the example of literary fiction and philological publications. An overview of trends in national periodicals is presented, bibliographic information in the literary and artistic and philological journals is analysed. Issues of transformation of literary magazines in the media sphere are revealed.